A low-cost and portable wrist exoskeleton using EEG-sEMG combined strategy for prolonged active rehabilitation - Yang, Shiqi; Li, Min; Wang, Jiale; Shi, Zhilei; He, Bo; Xie, Jun; Xu, Guanghua (Frontiers in Neurorobotics, 2023)
Hemiparesis is a common consequence of stroke that severely impacts the life quality of the patients. Active training is a key factor in achieving optimal neural recovery, but current systems for wrist rehabilitation present challenges in terms of portability, cost, and the potential for muscle fatigue during prolonged use. To address these challenges, this paper proposes a low-cost, portable wrist rehabilitation system with a control strategy that combines surface electromyogram (sEMG) and electroencephalogram (EEG) signals to encourage patients to engage in consecutive, spontaneous rehabilitation sessions. In addition, a detection method for muscle fatigue based on the Boruta algorithm and a post-processing layer is proposed, allowing for the switch between sEMG and EEG modes when muscle fatigue occurs. This method significantly improves accuracy of fatigue detection from 4.90% to 10.49% for four distinct wrist motions, while the Boruta algorithm selects the most essential features and stabilizes the effects of post-processing. The paper also presents an alternative control mode that employs EEG signals to maintain active control, achieving an accuracy of approximately 80% in detecting motion intention. Overall, the proposed system presents a promising approach to addressing the limitations of existing wrist rehabilitation systems.